Outlook of dengue in Malaysia: a century later - AbuBakar, Sazaly; Shafee, N. (2002)
Dengue continues to be a major health threat to Malaysia a century after its first reported outbreak in 1902. Examination of the available outbreak data suggested that a major DF/DHF outbreak occurred in Malaysia in a cyclical pattern of approximately every 8 years. All four dengue virus serotypes are found co-circulating in Malaysia, but after the first and only major outbreak involving DEN-4 in 1960's, only DEN-1, DEN-2 and DEN-3 were associated with DF/DHF outbreaks. It is argued that perhaps the spread of the later dengue virus serotypes followed the pattern of spread of the mosquito vector Aedes aegypti, whereas the former was associated with Aedes albopictus, the outdoor and rural area dwelling mosquito. Estimating from the trend and pattern of dengue and the associated dengue virus serotypes, unless there is a major breakthrough in dengue vaccine development, it is likely that dengue outbreaks will continue to occur in Malaysia throughout the 21st century.